Research on sustainable development of insurance property based on IDP model - Zheng, Yuekun (Transactions on Economics, Business and Management Research, 2024)
Extreme weather events are becoming homeowners and insurers. Insurance companies continue to face more and more serious claims, increasing the cost of payments. and it is difficult for insurance companies to accurately assess and quantify risks. In this paper, this text incorporate the Geography and Environment factors together with Economic factors to build an Insurance-Development-Protection Model (IDP Model) to help homeowners and insurance companies solve crises. IDP Model consists of three interlocking submodels. They are Insurance model, Real estate development model and Protection model. By factoring in some parameters, sustainability and equity are upgraded to priorities at the sacrifice of economic profit. The model help insurance companies maintain profitability among Insurance Development and protection and provide decision support to community leaders to ensure that community buildings are making the right decisions about current or future insurance coverage when they are affected by extreme weather.